Elevated glycated haemoglobin affects Achilles tendon properties and walking capacity in healthy people without a diagnosis of diabetes - Magris, Riccardo; Uchytil, Jaroslav; Cipryan, Lukáš; Skýpala, Jiří; Jandacka, Daniel; Monte, Andrea (Scientific reports, 2025)
The aim of this study was to test the hypothesis that individuals with an increase in HbA1c (i.e. above the regular but below the diabetic threshold) exhibit an impairment in the Achilles tendon structure and walking capacity, due to the adverse effect of the advanced glycation end-product. One hundred fifty-eight participants matched for gender, age, physical activity and BMI, were divided in two cohorts based on the HbA1c level: normal HbA1c (NGH; <39 mmol/molHb; n = 79) and altered HbA1c (AGH; >=39 mmol/molHb; n = 79). Each participant performed several walking trials to evaluate the kinematic parameters during walling at the self-selected speed and a quantitative MRI scan of the Achilles tendon (AT) to obtain its intrinsic characteristics (i.e. T2* relaxation time short and long component). The AT T2* relaxation time short component (a parameter related to the tendon collagen quality) was reduced in AGH compared to NGH. Furthermore, AGH exhibited a slower self-selected walking speed (NGH: 1.59 ± 0.18 m/s; AGH:1.54 ± 0.16 m/s) and a shorter stride length (NGH: 1.59 ± 0.13 m; AGH:1.55 ± 0.11 m). Our data suggest that a non-pathological increase in HbA1c is able to negatively affect AT collagen quality and walking capacity in healthy people. These results highlight the importance of glycemic control, even below the pathological threshold. Since diabetes could alter several biological pathways, further studies are necessary to determine which mechanisms and their timing, regarding the HbA1c rise, affect tendon composition and, consequently, walking capacity.
Keywords: biomechanika; lidé; magnetická rezonanční tomografie; Adult; Middle Aged; Walking; Achilles Tendon; Magnetic Resonance Imaging; diabetes mellitus; Female; chůze; Healthy Volunteers; Humans; Diabetes Mellitus; lidé středního věku; mužské pohlaví; Achillova šlacha; Biomechanical Phenomena; glykovaný hemoglobin; ženské pohlaví; Male; produkty pokročilé glykace; zdraví dobrovolníci pro lékařské studie; dospělí; Glycated Hemoglobin; Glycation End Products, Advanced